2012
DOI: 10.1136/annrheumdis-2011-200424
|View full text |Cite
|
Sign up to set email alerts
|

TNF blockade requires 1,25(OH)2D3 to control human Th17-mediated synovial inflammation

Abstract: These data show that TNF blockade does not suppress IL-17A and IL-22, which can be overcome by 1,25(OH)(2)D(3). The combination of neutralising TNF activity and 1,25(OH)(2)D(3) controls human Th17 activity and additively inhibits synovial inflammation. This indicates more valuable therapeutic potential of activation of Vitamin D receptor signalling over current TNF neutralisation strategies in patients with RA and potentially other Th17-mediated inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 43 publications
(57 reference statements)
6
51
0
2
Order By: Relevance
“…66 The importance of understanding the role of vitamin D in autoimmune diseases is enforced by the very high prevalence of hypovitaminosis D in this particular setting. 61,67 Relative hypovitaminosis D and secondary hyperparathyroidism in autoimmune rheumatic diseases An impairment of Vitamin D system has already been postulated as a concausal factor in the pathogenesis of osteoporosis in inflammatory arthritis.…”
Section: Vitamin D In Autoimmune Diseasesmentioning
confidence: 99%
“…66 The importance of understanding the role of vitamin D in autoimmune diseases is enforced by the very high prevalence of hypovitaminosis D in this particular setting. 61,67 Relative hypovitaminosis D and secondary hyperparathyroidism in autoimmune rheumatic diseases An impairment of Vitamin D system has already been postulated as a concausal factor in the pathogenesis of osteoporosis in inflammatory arthritis.…”
Section: Vitamin D In Autoimmune Diseasesmentioning
confidence: 99%
“…Recently, we showed that besides IL-17A, TNF-a was involved in the induction of the proinflammatory loop in Th17-RASF cultures (18,19). Furthermore, the combination of TNF-a and IL-17A blockade more strongly suppressed IL-6, IL-8, MMP-1, and MMP-3 production in these Th17-RASF cultures than blocking only IL-17A or only TNF-a (18).…”
Section: Combining Celecoxib and Tnf-a Blockade In Th17-rasf Culturesmentioning
confidence: 99%
“…This loop may be an important pathway in the progression of arthritis and possibly in other Th17 diseases as well. The autocrine IL-17A production by Th17 cells is critical to sustain the proinflammatory loop (18,19), but the mechanism underlying the autocrine IL-17A induction is still unknown.…”
mentioning
confidence: 99%
“…However, when an inflammatory response occurs, FLS become hyperplastic, invasive, and highly migratory, contributing to cartilage destruction and thus, RA [6, 7]. Van Hamburg et al reported that the combination of neutralizing TNF activity and 1,25-dihydroxyvitamin D 3 (1,25-(OH) 2 D 3 ) contribute to controlling human Th17 activity, which induces a pro-inflammatory feedback loop on RA synovial fibroblast interactions and inhibits synovial inflammation [8]. However, the specific mechanism of this function requires a further investigation.…”
Section: Introductionmentioning
confidence: 99%